The contribution of the Anglican church to education in the Cape - Rawlins, G E (Rhodes University, Faculty of Education, Department of Education, 1960)
In his "Onderwys in Kaapland, 1652 - 1939", Dr. P.S. du Toit makes special references to the educational work of the Anglican Church, indicating that there is some contribution. This attitude has as its aim to expose more of the reef of which the outcrops receive attention by Dr. du Toit ... much can happen between 1807 and 1829, and some of what did is described in these pages. One of Dr. du Toit's interests is the effect of the attempt to make English and instruction in English the basis of all education. Chap. 1, p. 1.
Keywords: Church and education -- South Africa; Church of England -- Education -- South Africa; Education -- South Africa -- Cape of Good Hope